(untitled) - Gelsey, James; Copyright Paperback Collection (Library of Congress) (New York, 2002)
Professor Pumpernickel has recreated an ancient civilization on a beautiful jungle nature preserve. A mysterious white gorilla starts terrorizing all the visitors - is the ghostly gorilla real?
"A little apple paperback."
"Cartoon network."
"RL2"--P. 4 of cover.
"006-009"--P. 4 of cover.
Keywords: Gorilla; Fiction; Radio and television novels; Children's stories; Fiction